Design of efficient Programming Language with Lexer using ’’-prefixed identifier - Gupta, Priya; Kumar, L S Yaswanth; Santosh, J V V M S D; Kumar, D Yashwanth; Dinesh, Chokkari; Venkata Chalapathi, Mukkoti Maruthi (EAI Endorsed Transactions on Scalable Information Systems, 2023)
An identifier which starts with ‘‘is known as ‘‘-prefixed identifier and this type of identifiers are used in our research paper to improve the lexical analysis phase. This paper talks about a new programming language with ‘‘-prefixed identifier that features a novel approach for optimizing the lexer for efficient lexical analysis which can be applied to any existing language. This approach is used to classify identifiers and keywords using ‘‘-prefixed variables, which significantly reduces the time taken and number of iterations required during the tokenization process, leading to improved overall performance. This type of language structure allows for fast lookup and matching of tokens. We conducted a series of experiments to evaluate the performance of our lexer and compared it with a regular lexer. Our results show that our approach leads to significant improvements in time complexity and number of iterations for identifying whether the token is an identifier or a keyword, resulting in faster compilation times and improved overall performance. Our language has reduced the amount of time taken by 7-10% and 45-50% in terms of iterations. Our language and lexer represent a significant step forward in the design and implementation of high-performance programming languages by reducing the number of iterations and time taken to identify whether a token is a keyword or an identifier.